161k views
0 votes
F(x) = x + 4 and g(x) = x - 1Step 3 of 4: Find (f 3)(x). Simplify your answer.Answer(f)(x) =

F(x) = x + 4 and g(x) = x - 1Step 3 of 4: Find (f 3)(x). Simplify your answer.Answer-example-1

1 Answer

6 votes

For this problem, we are given two functions, we need to determine the composite between these two expressions.

The two functions are:


\begin{gathered} f(x)=x+4\\ \\ g(x)=x-1 \end{gathered}

This composite is the product of the two functions, therefore we have:


\begin{gathered} (f\cdot g)(x)=(x+4)\cdot(x-1)\\ \\ (f\cdot g)(x)=x^2-x+4x-4\\ \\ (f\cdot g)(x)=x^2+3x-4 \end{gathered}

The answer is x²+3x-4.

User Tobriand
by
5.3k points